2016
DOI: 10.1007/s40264-016-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase (DPP)-4 Inhibitor-Induced Arthritis/Arthralgia: A Review of Clinical Cases

Abstract: Dipeptidyl peptidase (DPP)-4 inhibitors are a class of oral drugs used for the treatment of type 2 diabetes mellitus (T2DM). The pharmacological inhibition of DPP-4 seems to also induce adverse events related to cytokine-induced inflammation. Recently, several clinical cases regarding the association of DPP-4 inhibitors and the onset of arthritis/arthralgia have been reported in the literature. Various mechanisms could be responsible for DPP-4 inhibitor-induced arthritis/arthralgia, and the increase of cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…This study is part of a set of initiatives to promote drug safety developed by the Campania Pharmacovigilance Regional Centre during the last decade. 11,[25][26][27][28][29] By re-evaluating the ICSRs, we found that <2% of cases were deemed preventable. The most commonly detected preventable criterion was labelled drug-drug interaction of coadministered drugs with DAA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This study is part of a set of initiatives to promote drug safety developed by the Campania Pharmacovigilance Regional Centre during the last decade. 11,[25][26][27][28][29] By re-evaluating the ICSRs, we found that <2% of cases were deemed preventable. The most commonly detected preventable criterion was labelled drug-drug interaction of coadministered drugs with DAA.…”
Section: Discussionmentioning
confidence: 95%
“…This study is part of a set of initiatives to promote drug safety developed by the Campania Pharmacovigilance Regional Centre during the last decade . By re‐evaluating the ICSRs, we found that <2% of cases were deemed preventable.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, however, clinical evidence showing the epidemiological effect of DPP‐4 inhibitors on autoimmune diseases is scarce. In addition, several studies rather raised concerns about severe joint pain related to the use of DPP‐4 inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of DPP-4 have been associated with many processes that could lead to the development of arthritis 4 18–27. Some of these processes perform a pathologic function only in the setting of a genetic predisposition 17 24 28.…”
Section: Discussionmentioning
confidence: 99%